Adhesives Applications and Properties - Rudawska, Anna (IntechOpen, 2016)
This book presents some information regarding adhesives which have applications in industry, medicine and dentistry. The book is divided into two parts: "Adhesives Applications in Medicine and Dentistry" and "Properties of Adhesive." The aim of such a presentation is to present the usage in very different aspects of application of the adhesives and present specific properties of adhesives. Adhesives' advantageous properties and relatively uncomplicated processing methods contribute to their increasing application and their growing popularity in the industry, medicine and other branches. Some adhesives represent properties superior to those of most adhesive materials, due to their excellent adhesion and chemical resistance. A wide variety of adhesives' considerable flexibility in modification of properties of adhesives allows adjusting the composition to particular applications.